Research on large-signal stability of SOFC-lithium battery ship DC microgrid - Fang, Yibin; Yu, Wanneng; Liao, Weiqiang; Yang, Rongfeng; Luo, Chenghan; Zhang, Changkun; Dong, Xin (Frontiers in Energy Research, 2024)
Addressing the issue of grid oscillations arising from the susceptibility of DC microgrids to disturbances from impulsive loads, this paper proposes a stability criterion method based on mixed potential functions for solid oxide fuel cell (SOFC) systems. Firstly, a mathematical model of shipboard DC microgrids incorporating SOFC is established. Next, an analysis is conducted on the impact of SOFC fuel utilization rate and DC/DC controller parameters on system stability under impulsive load conditions. Subsequently, a stability criterion based on mixed potential functions for the system under large disturbances is constructed. Finally, simulation verification of the stability boundary conditions for SOFC systems operating either independently or in conjunction with lithium battery systems based on this criterion is performed. Experimental results validate the effectiveness of the proposed stability criterion and control strategies.